Creativity and Innovation in Language Materials Development and Language Teaching Methods In Asia and Beyond - SURI, ELDA MARTHA (journal of residu, 2018)
Education in Asia is undergoing changes as we move from the years tahunmencoba and test strategy learning rote and tried to create creative thinking skills. In order to encourage students to concentrate and participate in class, the teacher has to be creative and innovative. A wide range of materials and teaching methods should be explored where students come from backgrounds with different learning styles and different capabilities. The innovative teachers can retrieve information from text, audio and visual for the purpose of teaching. This paper is intended to inform, motivate and to explore the many possibilities to make teaching such a reality. This study aims to explore the patterns of thinking as a new model of learning used in learning in the classroom.